STUDI PENGELOLAAN AIR HUJAN DALAM RANGKA PENGEMBANGAN TAMAN KONSERVASI DI KOTA SAWAHLUNTO, SUMATERA BARAT - Kent, Steven; Yudianto, Doddi; Fitriana, Finna (Direktorat Bina Teknik Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2022)
Sawahlunto Conservation Park is an area developed for plant protection and tourism activities. The Sawahlunto city was initially built to support coal mining activities, so the conservation park has several basins that can be used as flood parking ponds. These basins can be used to meet the needs of watering plants. The study is used to examine the water availability and flood analysis at the area to be built. The conservation park is divided into three areas based on the four reservoirs location: the Kandih Park area, the northern and the southern part of the parking area. In this study, hydrologic and hydraulic analyses will be conducted. In the hydrological analysis, simulations of reservoir capacity are carried out to describe the amount of water that can be used every month. In the hydraulic analysis, SWMM program is used to model rainwater as surface runoff, estimate the planned channel dimensions, and reservoir flood volume. The reservoir simulation results show that the water needs for watering plants can be fully met. However, the available storage ponds have a much smaller volume than the rainfall volume, so the pond will run off throughout the year. The SWMM modeling results show that the channel dimensions from 0.2 m x 0.2 m to 0.5 m x 0.5 m, can drain flood discharge with a two-year return period, with a freeboard five-year return period. This study can be used as a guideline for developing conservation areas in reusing the potential of ex-mining land. Keywords: Conservation Park of Sawahlunto, Drainage Design, Rainfall Management, Reservoir Simulation, SWMM